Is a fan coil unit (FCU) an efficient cooling system for net-zero energy buildings (NZEBs) in tropical regions? An experimental study on thermal comfort and energy performance of an FCU - M.M.S. Dezfouli; A.R. Dehghani-Sanij; K. Kadir; R. Suhairi; Sh. Rostami; K. Sopian (Results in Engineering, 2023)
In tropical regions, the selection of an efficient cooling system is a prerequisite for energy-efficient and net-zero energy buildings (NZEBs), while fan coil unit (FCU) systems are commonly used to provide thermal comfort (TC) of the interior environment throughout the entire year. In this study, to find a cooling solution for Malaysia's first net-zero building, the performance of a case study FCU-classroom was evaluated based on a one-month experimental assessment and a one-year simulation function. The precision of the measurements was computed using uncertainty analysis, and the simulation model was validated using measurement data. The impact of mechanical dehumidification on FCU performance was evaluated by analyzing the collected data in terms of cooling load allocation, cooling coil capacity, TC, and energy consumption. In order to guide the selection of a cooling system, a comparative analysis has been conducted between the performance of the FCU and two alternative systems, namely the redesigned FCU and the desiccant cooling system. This analysis was focused on evaluating the TC and energy use of these systems. The findings from the FCU performance analysis indicated that, in order to handle the cooling load in a classroom with an equal distribution of latent and sensible load (50:50 ratio), the FCU utilized 56 % of its total cooling coil capacity (13.06 kW) and 37 % of its energy consumption for the dehumidification process. The FCU utilized an average of 1360.3 kWh per month to maintain a comfortable room temperature of 24.3 °C and an uncomfortable relative humidity (RH) of 77.2 %. However, it was observed that the amount of moisture removal was insufficient to achieve a humidity comfort level in the room. Comparing alternative solutions to the FCU revealed that while a redesigned could provide TC, it consumed approximately 1.6 times more energy per month than the FCU. The desiccant cooling system provided TC with an average monthly energy savings of 37.8 % compared to the case study FCU.